P228 Preliminary Evaluation of a new immunofluorescence mosaic assay for inflammatory bowel disease diagnosis: a pilot study in Udine. (25th January 2019) - Fabris, M; Meroi, F; Cifu', A; Castagnaviz, E; Curcio, F; Terrosu, G; Scardino, G; Vadalà di Prampero, S F; Marino, M
Abstract: Background: Inflammatory bowel disease (IBD) is characterised by a broad spectrum of clinical phenotypes with different outcomes. To improve disease management, we need specific biomarkers, either to help differential diagnosis and to identify early patients with worse prognosis. Several new IBD-associated autoantibodies have been recently proposed, in particular anti-pancreatic glycoproteins (PAB) antibodies appear highly promising as diagnostic and prognostic tool in Crohn's disease (CD). 1 In this pilot study, we aimed to test the analytical performances of a combined panel of new and classical antibodies associated with chronic inflammatory bowel diseases (IBD) in a well selected series of patients diagnosed as CD or ulcerative colitis (UC). Methods: We enrolled 80 patients with IBD (40% females; mean age 43 ± 15 years), comprising 57 CD and 23 UC. Sera were collected and stored at −20°C until analysis. As controls, we enrolled 20 age- and sex-matched blood donors (BDs). All sera were tested for: anti-PAB antibodies (anti-GP2 and anti-CUZD1), anti-goblet cells antibodies, anti-saccharomyces cerevisiae antibodies (ASCA) and lactoferrin-specific P-ANCA, using indirect immunofluorescence (IIF) according to manufacturer's instructions (Euroimmun CIBD profile, Germany). The slides contained a biochip mosaic consisting of PAB-transfected HEK293 cells (a mixture expressing recombinant CUZD1 or GP2), mock-transfected control cells, goblet cells, ethanol fixed human granulocytes, lactoferrin-specific (LFS) human granulocytes and, in a separate incubation field, a smear of saccharomyces cerevisiae. Both IgG and IgA antibodies were evaluated at proper dilutions. Results: Overall, positive anti-PAB IgG and/or IgA antibodies were found in 16/57 (28.1%) CD patients vs. 0/23 UC (OR 18.7, 95% CI 1.1–326; p = 0.004) and 0/20 BDs (specificity 100%). The combined presence of anti-CUZD1 and anti-GP2 antibodies were recorded only in 3 samples; in the others, only one of the anti-PABs was present. Of note, 5/16 (31%) aPAB+ patients were ASCA negative and all presented colonic or ileocolonic localisation: in these cases aPAB would be highly useful to make differential diagnosis with UC. ASCA resulted positive in 40/57 (70.1%) CD patients vs. 2/23 (8.7%) UC and 2/20 (10%) BDs. A positive IIF reactivity in LFS-granulocytes was observed in 14/57 (24.6%) CD patients vs. 14/23 (60.9%) UC and 0/20 (0%) BDs. Anti-goblet cells resulted always negative. Conclusions: The combined assessment of several markers of IBD by this new mosaic IIF assay appeared highly promising to improve the characterisation of CD and UC patients, both for diagnosis and prognosis. Reference 1. Papp M, Sipeki N, Tornai T, et al. Rediscovery of the anti-pancreatic antibodies and evaluation of their prognostic value in a prospective clinical cohort of Crohn's patients: the importance of specific target antigens [GP2 and CUZD1]. J Crohns Colitis 2015;9:659–68.